7(7c+1)-4c=12(3c-2)

Simple and best practice solution for 7(7c+1)-4c=12(3c-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(7c+1)-4c=12(3c-2) equation:



7(7c+1)-4c=12(3c-2)
We move all terms to the left:
7(7c+1)-4c-(12(3c-2))=0
We add all the numbers together, and all the variables
-4c+7(7c+1)-(12(3c-2))=0
We multiply parentheses
-4c+49c-(12(3c-2))+7=0
We calculate terms in parentheses: -(12(3c-2)), so:
12(3c-2)
We multiply parentheses
36c-24
Back to the equation:
-(36c-24)
We add all the numbers together, and all the variables
45c-(36c-24)+7=0
We get rid of parentheses
45c-36c+24+7=0
We add all the numbers together, and all the variables
9c+31=0
We move all terms containing c to the left, all other terms to the right
9c=-31
c=-31/9
c=-3+4/9

See similar equations:

| 3(7x+28)=105 | | 4x/7-10=30 | | 8x-5x-5=7 | | 26x^2+23x+5=0 | | 7x-3x-5=(-17) | | 4q=-q+9 | | (x+8)2=16x | | -3p^2-5p+8=0 | | 13-5x=-24+3x | | 4-(x)+10=12 | | 12/18=9/6x | | 27-3x=-3-7x | | x^2=0.00001 | | 7x÷4-4x=3 | | 50x+120(92•x)=8380 | | 5p=3p | | 76=1/2(10p+2) | | x+3/5=1/3x+3/10 | | 13/11=u/9 | | z+84=50 | | -1x-5=-8x-47 | | -3(2x+3)=-5(x+1)-2 | | z+17+28=85 | | (x-80)/2=57 | | z+28=85 | | z+52=90 | | z+54=90 | | 9x=-9x+90 | | 54+90=z | | 10(x^2-1)=0 | | a+2a+2a+5=100 | | 54+180=y |

Equations solver categories